Production of Drug Delivery Systems Using Fused Filament Fabrication: A Systematic Review - Bahaa Shaqour; Aseel Samaro; Bart Verleije; Koen Beyers; Chris Vervaet; Paul Cos (Pharmaceutics, 2020)
Fused filament fabrication (FFF) 3D printing technology is widely used in many fields. For almost a decade, medical researchers have been exploring the potential use of this technology for improving the healthcare sector. Advances in personalized medicine have been more achievable due to the applicability of producing drug delivery devices, which are explicitly designed based on patients’ needs. For the production of these devices, a filament—which is the feedstock for the FFF 3D printer—consists of a carrier polymer (or polymers) and a loaded active pharmaceutical ingredient (API). This systematic review of the literature investigates the most widely used approaches for producing drug-loaded filaments. It also focusses on several factors, such as the polymeric carrier and the drug, loading capacity and homogeneity, processing conditions, and the intended applications. This review concludes that the filament preparation method has a significant effect on both the drug homogeneity within the polymeric carrier and drug loading efficiency.